GIRT scientific divers citizen science programme: Volunteer motivations and characteristics. - Viduka, Andrew; Edney, Joanne (Journal of Community Archaeology & Heritage, 2022)
The no-impact maritime archaeological conservation-focused citizen science programme gathering information via recreational and technical (GIRT) scientific divers formally started in January 2019 and was designed and developed to encourage interested people, businesses, and groups to have an active and positive maritime archaeology management role. Initially launched in New Zealand and Australia, GIRT has expanded to include members in 9 countries. To better understand who is interested to participate in GIRT, why, and what it is they seek to get out of their participation, a survey was sent out to the first 119 people who undertook training. 100 people responded to the survey providing information about the demographics of participants, their background in heritage and protection, diving, science and conservation, and volunteering. Survey results show that GIRT is acting as a gateway into maritime archaeology for individuals who have never dived wrecks and for people interested in natural heritage.